Do Migrants Really Foster Trade? The Trade-Migration Nexus, a Panel Approach 1960-2000 - Parsons, Christopher R. (World Bank, Washington, DC, 2012)
Despite the burgeoning empirical literature providing evidence of a strong and robust positive correlation between trade and migration, doubts persist as to unobserved factors which may be driving this relationship. This paper re-examines the trade-migration nexus using a panel spanning several decades, which comprises the majority of world trade and migration in every decade. First the findings common to the literature are reproduced. Country-pair fixed effects are then used to account for unobserved bilateral factors, the implementation of which removes all of the positive impact of migration on trade. In other words the unobserved factors, a leading candidate for which it is argued is international bilateral ties, are on average strongly and positively correlated with migrant networks. Dividing the world into the relatively affluent North and poorer South, the results show that migrants from either region only affect Northern exports to the South. This is intuitive since in general countries of the North export more differentiated products and information barriers between these regions are greatest. A country-level analysis further shows that migrants may both create and divert trade. Taken as a whole, the results demonstrate the large biases inherent in cross-sectional studies investigating the trade-migration nexus and highlight the extent to which previous results have been overstated.